2019
DOI: 10.1038/s41419-019-1443-2
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-184 promotes apoptosis of trophoblast cells via targeting WIG1 and induces early spontaneous abortion

Abstract: Recurrent spontaneous abortion (RSA) refers to the unintentional termination of two or more consecutive pregnancies that severely threatens human reproductive health. Our previous study has shown that miR-184 is expressed more highly in RSA than in normal pregnancy, whether in the villus or decidua. In this study, compared with normal pregnant women, the expression of miR-184 in decidual stromal cells (DSCs) and decidual immune cells (DICs), as well as in peripheral blood, from RSA patients was enhanced simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 25 publications
(27 reference statements)
1
44
0
Order By: Relevance
“…Li et al (33) reported that knockdown of Storkhead-box protein 1 induced apoptosis and decreased the migration and proliferation of HTR-8/SVneo cells via mediating the PI3K/AKT signaling pathway (33). A previous study also reported that miR-184, which is highly expressed in RSA, repressed the proliferation and promoted the apoptosis of trophoblast cells by targeting WIG1 and upregulating its downstream molecule Fas (7). Dong et al (8) also found that miR-520, which is highly expressed in villi in RSA, enhanced the apoptosis of human trophoblast cells by targeting and regulating PARP1 expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Li et al (33) reported that knockdown of Storkhead-box protein 1 induced apoptosis and decreased the migration and proliferation of HTR-8/SVneo cells via mediating the PI3K/AKT signaling pathway (33). A previous study also reported that miR-184, which is highly expressed in RSA, repressed the proliferation and promoted the apoptosis of trophoblast cells by targeting WIG1 and upregulating its downstream molecule Fas (7). Dong et al (8) also found that miR-520, which is highly expressed in villi in RSA, enhanced the apoptosis of human trophoblast cells by targeting and regulating PARP1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…The cellular mechanisms underlying recurrent abortion are the proliferation and apoptosis of cytotrophoblasts and human decidual cells (6). Zhang et al (7) reported that microRNA (miR)-184 is highly expressed in decidual stromal cells, decidual immune cells and peripheral blood of patients who experience recurrent spontaneous abortion (RSA). Mechanically, miR-184 promotes apoptosis and inhibits the proliferation of trophoblast cells by targeting and regulating WIG1 (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…miRNAs are noncoding endogenous RNA molecules with a length of 18~25 nucleotides, which are partially or completely complementary to the 3 ′ or 5 ′ untranslated region (UTR) of target genes [1,2]. miRNAs play a vital role in a wide range of biological processes including cell proliferation, differentiation, and apoptosis [3][4][5][6][7]. In addition, increasing evidences have been revealed demonstrating that the occurrences of many diseases including cancers are closely associated with abnormal expression of specific miRNAs [8], e.g., prostate cancer-associated miR-21 and miR-141 [9], breast cancer-associated miR-155-3p [10], and liver fibrosis-associated miR-378 [11].…”
Section: Introductionmentioning
confidence: 99%
“…There is actually no report on expression and function of miR‐184‐3p in the heart. A very recent study showed that miR‐184 promotes the repression of trophoblast cells proliferation inducing their apoptosis . It is possible that combination of different miRNAs overexpression and/or downregulation is beneficial as a therapeutic treatment of AF.…”
mentioning
confidence: 99%